The influence of substrate location and deposition time on ZnO nanostructures - Al-Azri, K.; Nor, Roslan Md; Al-Ruqeishi, M.S.; Amin, Y.M. (Faculty of Science, University of Malaya, 2010)
A study on the formation of ZnO nanostructures using the carbothermal evaporation method without catalyst and at atmospheric argon pressure has been conducted. The effects of the position of the substrates to the source and deposition time were investigated. The results of these parametric studies based on field-emission scanning electron microscopy (FESEM), Energy dispersive X-ray spectroscopy (EDX) spectrum and X-ray diffraction (XRD) analyses support the reduction-evaporation model for ZnO nanostructures formation using carbothermal evaporation.